The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1590/1519-6984.247915
|View full text |Cite
|
Sign up to set email alerts
|

Wild birds trade in Dera Ismael Khan and Bannu divisions of Khyber PakhtunKhwa (KPK) Province, Pakistan

Abstract: Wildlife trade is a profitable economic activity. Birds are among the most heavily traded animals worldwide, with numerous species threatened by pet trade. The present case study was stretched for period of one year to find out the status of wild birds’ trade in Bannu and Dera Ismael Khan Divisions. The study was aimed to find out the types of species, commercial prices of bird, trade routes, overall income generated from birds’ trade and the status of dealers whether licensed or not. Bimonthly visits were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Many traders mentioned that catching birds using locally made traps is easy, which motivates hunters to catch live birds and trade them in the local markets. Similar patterns of markets being dominated by bird trade have also been recorded in other parts of South Asia, such as Pakistan (Hussain & Khan, 2021). High demand for birds, the small capital investment required, their high abundance in local forests, the lack of awareness of laws on legality of trade, and the ease with which they can be hunted/caught, carried and concealed were the prime causes of the high level of bird trade in all of the markets we studied.…”
Section: Discussionsupporting
confidence: 68%
“…Many traders mentioned that catching birds using locally made traps is easy, which motivates hunters to catch live birds and trade them in the local markets. Similar patterns of markets being dominated by bird trade have also been recorded in other parts of South Asia, such as Pakistan (Hussain & Khan, 2021). High demand for birds, the small capital investment required, their high abundance in local forests, the lack of awareness of laws on legality of trade, and the ease with which they can be hunted/caught, carried and concealed were the prime causes of the high level of bird trade in all of the markets we studied.…”
Section: Discussionsupporting
confidence: 68%
“…This is due to hunting of wildlife for subsistence and trade is a widespread phenomenon, especially across tropical Southeast Asia [6,7]. Hussain and Khan [8] reported that wildlife has changed its dimension in recent years from subsistence to commercial trade and Southeast Asia is the epicenter of wildlife trade. This results in large quantities of wild animals are now on the brink of extinction, such as Chinese pangolin (Manis pentadactyla) and tiger (Panthera tigris) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3A presents the breakdown of wildlife utilization across different taxonomic groups, including mammals, reptiles, amphibians, and birds. In terms of food, mammals have the highest number of species utilized (15), followed by reptiles (8). Amphibians and birds have comparatively fewer species utilized for food, with one and two, respectively.…”
Section: Introductionmentioning
confidence: 99%